Implementasi Metode Yanbu’a dalam Memberantas Buta Huruf Al Quran di Era Digitalisasi Peserta Didik Kelas VII SMP YPVDP Bontang Tahun Pelajaran 2023/2024 - MW, Syafra’ie; Husain, Ahmadi (NABAWI: Jurnal Penelitian Pendidikan Islam, 2024)
This research discusses the implementation of the Yanbu'a method in eradicating Al Quran illiteracy in the era of digitalization. Aims to understand and determine the implementation of the Yanbu'a method in eradicating Al Quran illiteracy in the era of digitalization. Qualitative research methods. Data collection techniques using observation, interviews and documentation to analyze data related to the Yanbu'a method with the subject of class VII YPVDP Bontang Middle School students. The results of this research by breaking down Al Quran material into smaller parts and grouping them according to ability level can build togetherness and make it easier to understand. The implementation of the Yanbu'a method has succeeded in providing an effective approach and learning in eradicating students' Al Quran illiteracy so that currently no one has difficulty reading and writing the Al Quran properly and correctly. Even in this era of digitalization, this method is able to keep pace with advances in digital technology by using it in the Yanbu'a application. Thus, it can be concluded that in implementing the Yanbu'a method, researchers found indicators of success in eradicating Al Quran illiteracy, these indicators can be seen from the decreasing number of students who experience Al Quran illiteracy and the increasing achievements achieved.